TINJAUAN YURIDIS TERHADAP FUNGSI NOTARIS DALAM PERALIHAN HAK ATAS MEREK - Andhita Fatmawati (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract A form of the results of operations or trading services can be referred to as Trademarks or service brand. The meaning of